Tackling TB in low-incidence countries: improving diagnosis and management in vulnerable populations. (March 2017) - Heuvelings, C.C.; de Vries, S.G.; Grobusch, M.P.
Abstract: In low tuberculosis incidence regions, tuberculosis is mainly concentrated among hard-to-reach populations like migrants, homeless people, drug or alcohol abusers, prisoners and people living with HIV. To be able to eliminate tuberculosis from these low incidence regions tuberculosis screening and treatment programs should focus on these hard-to-reach populations. Here we discuss the barriers and facilitators of health care-seeking, interventions improving tuberculosis screening uptake and interventions improving treatment adherence in these hard-to-reach populations.